Poikilodermatous mycosis fungoides with erosive lesions - Anuradha A Bhide; Poonam C Singh; Mahendra M Kura (Wolters Kluwer Medknow Publications, 2019)
Mycosis fungoides (MF) is the commonest form of cutaneous T-cell lymphoma. Many clinical subtypes and variants of MF have been described, one of which is poikilodermatous MF variant. Erosions and bullous lesions in a patient with poikilodermatous MF is a rare presentation. We present one such rare case of poikilodermatous MF with erosive lesions in a 40-year-old male.